2018
DOI: 10.1029/2018gl077092
|View full text |Cite
|
Sign up to set email alerts
|

Summer Drivers of Atmospheric Variability Affecting Ice Shelf Thinning in the Amundsen Sea Embayment, West Antarctica

Abstract: Satellite data and a 35-year hindcast of the Amundsen Sea Embayment summer climate using the Weather Research and Forecasting model are used to understand how regional and large-scale atmospheric variability affects thinning of ice shelves in this sector of West Antarctica by melting from above and below (linked to intrusions of warm water caused by anomalous westerlies over the continental shelf edge). El Niño episodes are associated with an increase in surface melt but do not have a statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 45 publications
0
39
1
1
Order By: Relevance
“…The influence of tropical variability on West Antarctic climate varies by season and by tropical basin (Yuan et al, 2018), obscuring individual signals that could be used for future predictions. Several studies have demonstrated that the El Niño Southern Oscillation (ENSO) significantly influences West Antarctic climate and ice sheet mass balance by forcing interannual changes in the position and intensity of the Amundsen Sea Low (ASL; Clem et al, 2017;Deb et al, 2018;Fogt et al, 2012;Hosking et al, 2013;Paolo et al, 2018;Raphael et al, 2016). More recent studies have emphasized that low-frequency tropical variability, namely, the Pacific Decadal Oscillation (PDO)/Interdecadal Pacific Oscillation (IPO; Clem & Fogt, 2015;Meehl et al, 2016;Purich et al, 2016) and the Atlantic Multidecadal Oscillation (Li et al, 2014), may also affect West Antarctic climate on decadal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of tropical variability on West Antarctic climate varies by season and by tropical basin (Yuan et al, 2018), obscuring individual signals that could be used for future predictions. Several studies have demonstrated that the El Niño Southern Oscillation (ENSO) significantly influences West Antarctic climate and ice sheet mass balance by forcing interannual changes in the position and intensity of the Amundsen Sea Low (ASL; Clem et al, 2017;Deb et al, 2018;Fogt et al, 2012;Hosking et al, 2013;Paolo et al, 2018;Raphael et al, 2016). More recent studies have emphasized that low-frequency tropical variability, namely, the Pacific Decadal Oscillation (PDO)/Interdecadal Pacific Oscillation (IPO; Clem & Fogt, 2015;Meehl et al, 2016;Purich et al, 2016) and the Atlantic Multidecadal Oscillation (Li et al, 2014), may also affect West Antarctic climate on decadal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…When estimating decadal mass rates over individual regions, the Antarctic Peninsula and West Antarctica exhibit negative mass trends dominated by glacial discharge from melting and calving events of large ice streams and ice shelves (Gardner et al, 2018;Holland et al, 2010;Mouginot et al, 2014;Rignot et al, 2013), whereas East Antarctica has experienced a slight mass gain due in part to an increase in precipitation rates (Medley et al, 2018;Shepherd et al, 2012;Shepherd et al, 2018). The effect of ENSO on Antarctica has also been associated with anomalies in sea surface temperature and sea ice extent (Kwok et al, 2016;Pope et al, 2017), ice-shelf thinning rates (Deb et al, 2018;Paolo et al, 2018;Walker & Gardner, 2017), and surface melt events (Scott et al, 2019;Tedesco & Monaghan, 2009). moisture transport over the Amundsen Sea (Chen et al, 1996;Cullather et al, 1996;Sasgen et al, 2010;Turner, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…moisture transport over the Amundsen Sea (Chen et al, 1996;Cullather et al, 1996;Sasgen et al, 2010;Turner, 2004). The effect of ENSO on Antarctica has also been associated with anomalies in sea surface temperature and sea ice extent (Kwok et al, 2016;Pope et al, 2017), ice-shelf thinning rates (Deb et al, 2018;Paolo et al, 2018;Walker & Gardner, 2017), and surface melt events (Scott et al, 2019;Tedesco & Monaghan, 2009). Boening et al (2012) showed that the presence of a seesaw pattern of high and low pressure systems over Dronning Maud Land following the 2009-2010 El Niño led to increased cloud formation and subsequent precipitation in this sector.…”
Section: Introductionmentioning
confidence: 99%
“…Interannual and decadal variability in the tropical Pacific affects air temperature (Ding et al, 2011), snowfall (Bromwich et al, 2000;Cullather et al, 1996;Genthon and 80 Cosme, 2003), sea ice extent (Pope et al, 2017;Raphael and Hobbs, 2014) and upwelling of circumpolar deep water favoring ice-shelf basal melting (Dutrieux et al, 2014;Steig et al, 2012;Thoma et al, 2008) in West Antarctica. Recent studies found concurrences between El Niño events and summer surface melting over West Antarctic ice shelves (Deb et al, 2018;Nicolas et al, 2017;Scott et al, 2019). These connections are generally explained in terms of Rossby wave trains excited by tropical convection during 85…”
Section: Introductionmentioning
confidence: 92%